When it comes to cyber security, ignorance isn't bliss – it's negligence. Issue 12 (December 2020) - Sangster, Mark
Abstract : Given the rise of cybercrime targeting many small to medium-sized businesses (SMBs), the vast majority find themselves completely unprepared, having laboured under the misguided belief that they are too small to become a target of cybercrime. Rather than being too big to fail, they think they are too small to be noticed. The rise of cybercrime targeting small to medium-sized businesses (SMBs) has left many of them unprepared, believing they are too small to be a target. Most SMBs are left in the dark as to their actual risk and ignore the threat until it's too late. By failing to understand their true cyber risk, these firms often neglect their obligations and spending when it comes to preventing cyber breaches. One solution may be to turn to managed detection and response (MDR) providers, but this requires care, explains Mark Sangster of eSentire.